Maximising Diesel Generator Fuel Efficiency with LTO Battery Integration - Beković, Miloš; Sukič, Primož; Pintarič, Matej; Petrič, Luka; Štumberger, Gorazd (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Diesel generators are indispensable in areas lacking electricity infrastructure or requiring alternative power sources. However, while they offer significant advantages, they also suffer notable drawbacks, particularly in fuel efficiency during lower loads. Typically, generators operate in tandem with load profiles, resulting in inefficient operation during reduced loads. This article proposes a solution by integrating generator operation with a battery system. By combining the generator with batteries during periods of lower efficiency, we aim to enhance overall system efficiency.